Purification and characterization of DNA from whole blood of children with ALL and normal children - AL-Rubaee, Eaman A. S. (Journal of the Faculty of Medicine Baghdad, 2005)
Summary:Background: The acute lymphocytic leukemias (All) make up about 76% of children leukemias . lymphoid leukemias occur more often than expected in patients with immunodeficiency , chromosomal abnormalities & ataxia telangiectasia . A number of chnges occur in preneoplastic & neoplastic cells as the progress towards a greater degree of malignancy . Nuclear DNA may be used as an aid in diagnosis , to predict prognosis & to determent of certain neoplasia.Aim of the work: is to purify DNA from whole blood of predict & normal children & to characterize it by spectral studies.Patients & Methods: Fifteen EDTA-treated blood samples of children with acute lymphoblastic leukemia (ALL) and the same number from normal children were used to isolate DNA from whole blood, then to characterize and compare the DNA of ALL patients with normal individuals. Typical ratio of260nm/280nm absorbance ( used to assess purity ) for DNAResults: purified were 1.5 and 1.3 for ALL patients and normal children respectively. No real differences between DNA of ALL patients and normal DNA, when characterized by using UV spectrum at PH (7), were found. Infrared spectroscopy in the 4000-200 cm'1 region was used to characterize the DNA structure of ALL patients and normal children. A set of IR bands characterize of DNA conformations was proposed.